Development aspects of a high temperature heat pipe heat exchanger for high temperature gas-cooled nuclear reactor systems - Laubscher, Ryno (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.